Polypoidal Choroidal Vasculopathy: An Update on Therapeutic Approaches - Raymond L.M. Wong; Timothy Y.Y. Lai (Journal of Ophthalmic & Vision Research, 2013)
Polypoidal choroidal vasculopathy (PCV) is a retinal disease involving the choroidal vasculature characterized by the presence of polypoidal lesions with or without branching vascular network best seen on indocyanine green angiography (ICGA). Clinical features of PCV include recurrent subretinal hemorrhage; serosanguineous pigment epithelial detachment, subretinal exudation and serous retinal detachment. PCV is more prevalent among Asians and Blacks as compared to Caucasians and has been found to account for 25 to 50% of cases of presumed neovascular age-related macular degeneration in Asian patients. Treatment is indicated in patients with symptomatic PCV due to potentially irreversible visual loss. Various treatment modalities for symptomatic PCV have been described in the literature, including thermal laser photocoagulation, ICGAguided photodynamic therapy (PDT) with verteporfin, anti-vascular endothelial growth factor (VEGF) therapy, and combined PDT and anti-VEGF therapy. This review aims to provide an update on the therapeutic options for PCV, with particular reference to recent studies published in the past two years.